Russia and the diffusion of political norms: the perfect rival?. Issue 3 (3rd April 2022) - Casier, Tom
ABSTRACT: Russian norm diffusion has been studied mainly as the mirror image of the EU's, but deserves to be studied in its own right and complexity. Three core categories of political norms are explored: sovereign choice, regime and conservative ideas. It is argued that Russia does not promote a coherent political model, by lack of one, but rather diffuses a disparate set of conservative ideas and non-democratic practices. Russia's normative positioning is equivocal. It champions established international norms like sovereignty, placing itself within the dominant normative community, but contesting the application by the West. When it comes to certain liberal political norms (often reduced to a strawman version), it questions their validity and rejects them, placing itself outside the dominant normative community, but claiming to defend "genuine" European values. This makes Russia an ambiguous norm contester, rather than the perfect normative rival of the EU. The complexity of its norm contestation follows from exogenous motives: it is predominantly an anti-hegemonic reaction against what it perceives as the Western imposition of norms, harming vital Russian interests.